Rapporti di genere e “balli sardi”. Il femminile tra piacere e potere nel campo coreutico della Sardegna centro-meridionale - Deiana, Alessandro (EtnoAntropologia, 2021)
The article deals with gender relations in “traditional” Sardinian dances and explores their asymmetrical and hierarchical form, an issue rarely considered by dance anthropology and gender studies in Italy. Using an ethnographic perspective, it focuses on practices and discourses related to “ballo sardo”, a dance where man usually plays a leading role in terms of dance guidance, control of execution, and freedom of expression. Giving voice to the point of view of the female dancers, so far invisibilized, the article intends to show how gender relations operate in Sardinian dances, and tries to explain some of the mechanisms that govern the reproduction and naturalization of gender relations through a popular dance.